Dye-Sensitized Solar Cells with Modified TiO2 Scattering Layer Produced by Hydrothermal Method - Lin, Yu-Shyan; Chen, Wei-Hung (Materials, 2025)
This work proposes dye-sensitized solar cells (DSSCs) with various photoanode designs. A hydrothermal method is used to synthesize hydrangea-shaped TiO2 (H-TiO2) aggregates. The X-ray diffraction (XRD) pattern of H-TiO2 reveals only an anatase phase. No peaks of any other phases are detected, indicating that the hydrangea-shaped TiO2 is phase-pure. The size of the synthesized H-TiO2 is approximately 300 nm to 2 μm, and its particle size is suitable for use in the scattering layer of a DSSC. Mixing the P25 TiO2 into the H-TiO2 aggregate with the best mixing ratio can significantly improve the conversion efficiency of DSSCs. When the ratio of H-TiO2:P25 TiO2 = 3:7, the scattering layer has the optimal parameters, as determined experimentally. The optimal structure is a double layer that is formed of five layers of P25 TiO2 plus a single scattering layer. An open circuit voltage (Voc) of 0.77 V, short-circuit current (Jsc) of 15.26 mA/cm2, fill factor (FF) of 0.71, conversion efficiency (η) of 8.33%, and charge-collection efficiency (ηcc) of 0.96 are obtained from the optimally designed photoelectrode. To the best of the authors’ knowledge, this work is the first in which large particles of hydrangea are mixed with small particles of P25 TiO2 in various proportions to form a scattering layer.